Memorial of the Chesapeake and Ohio Canal Company, for a loan from the State (Document (Virginia. General Assembly) ;, 1849)
1849? Memorial of the Chesapeake and Ohio Canal Company to the General Assembly, requesting a loan from the state to complete the work on its canal between dam No. 6 and Cumberland.